Performance Comparison of Pure Electric Vehicles with Two-Speed Transmission and Adaptive Gear Shifting Strategy Design - Bolin He; Yong Chen; Qiang Wei; Cong Wang; Changyin Wei; Xiaoyu Li (Energies, 2023)
The two-speed automatic transmission can adjust the drive motor speed of electric vehicles and expand their output torque range. This study proposes a rule-based partitioned gear-shifting strategy for pure electric vehicles equipped with a two-speed dual-clutch transmission, combining economic and dynamic shifting strategies to ensure low energy consumption and strong power. Specifically, fuzzy logic is applied to adaptively modify the partition shifting strategy online, to reduce invalid gearshifts, increase the service life of the transmission, and improve driving comfort. Finally, we compare the economic performance and dynamic performance of pure electric vehicles equipped with a two-speed dual-clutch transmission and a single-speed final drive. The results show that the vehicle equipped with the two-speed dual-clutch transmission has better economic and dynamic performance. In addition, its maximum climbing ability was verified by rig testing. These results prove that the two-speed dual-clutch automatic transmission and the gear-shifting strategy proposed in this study can comprehensively improve the performance of pure electric vehicles.